NEW WAYS TO PROMOTE CASTOR SEED PRODUCTION IN BRAZIL - Pina, Michel; S. Severino, Liv; E. M. Beltrão, Napoleão; Villeneuve, Pierre; Lago, Regina (Science & Technology Journals, 2005)
Thirty years ago, Brazil was the world’s biggest producer of castor beans/castor oil. For various reasons, the areas cultivating castor beans were substantially reduced, and it is now a distant third behind the principal producers, India and China. Castor oil is a very strategic industrial raw material, but its production is complicated by the presence of toxic substances and allergens in the beans and thus in the seed cake by-product of oil extraction. Castor plants are suitable for semiarid zones and for small producers. The European Union, especially France, has successfully attempted cultivation of this plant but for the reasons above-mentioned decided to limit itself to importing castor oil. As part of a scientific agreement, Embrapa (through Labex) and Cirad (through its fat and oil research team) considered ways of contributing to the resumption of castor bean production in Brazil. The following possibilities are being or can be explored: a new concept for oil extraction (using acetone as the solvent) with the simultaneous production of an oilseed cake with reduced or no allergenic problems; lipase production from this biomass as well as the production of high value biomolecules. Methods of adding value to the oilseed cake that could be pursued involve the development of cooking-extrusion, or other processes to increase its utilisation as feed and manure. On the other hand, the expression of allergen-free genetic material is also worth considering. Finally, the production of CLA (conjugated linoleic acids), which have nutritional and therapeutic properties, represents another way of promoting the castor crop since these can be directly obtained from castor oil dehydration, under suitable catalysis, at competitive prices.